PENGARUH LATIHAN FARTLEK TERHADAP DAYA TAHAN AEROBIK TIM FUTSAL KELUARGA KITA 217 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is that the endurance of the Aerobics of Futsal Keluarga Kita 217 Pekanbaru athletes is still less than optimal, seen during the second half the players began to experience fatigue, unable to regulate breathing, skills, teamwork began to be invisible so that the ball was easy seized by the opponent and attacked players Futsal Keluarga Kita 217 Pekanbaru players slowly descended into their own area. To fix this problem, the writer gives a form of exercise that increases aerobic endurance, namely Fartlek training. The title raised in this study is